Presence of the Anopheles culicifacies complex species A in southeast Iran - Seyed Massoud Madjdzadeh; Nahid Behi; Mohammad Amin Gorouhi; Arsalan Amirkafi; Mohammad Ali Oshaghi (Tropical Medicine and Health)
Abstract Background The Anopheles culicifacies complex is one of the most important malaria vectors in Southeast Asia and Southeastern Iran. Although the sibling species within this complex are morphologically indistinguishable, they differ significantly in their disease transmission potential, blood-feeding behaviour, and other biological traits. Cytogenetic and chromosomal studies have identified five sibling species within this complex: A, B, C, D, and E. Understanding the species composition and distribution of this complex is crucial for malaria control strategies. Objectives This study aimed to identify the sibling species of the An. culicifacies complex in Qaleh Ganj County, Kerman Province, Southeastern Iran. Specifically, the study sought to determine the presence of species A, which is known to be a primary vector of malaria in the region. Methods We employed allele-specific PCR and sequencing PCR techniques to identify the sibling species. DNA was extracted from mosquito specimens, and the D3 region of the 28S rDNA gene and a segment of the COII gene from the mitochondrial genome (mtDNA) were targeted for amplification and sequencing. Results Data analysis revealed a positive correlation between An. culicifacies s.l. specimens and altitude, with most specimens collected from mountainous areas. Both allele-specific PCR and sequencing PCR confirmed the presence of species A in the study areas of Kerman Province. Conclusions Given that species A is a primary malaria vector, the findings of this study provide valuable insights for guiding malaria control strategies in Southeastern Iran. Further studies are recommended to assess the vector competence and ecological dynamics of other species within the An. culicifacies complex in the region.